Implementation Of Boarding School Management At Madrasah Aliyah Negeri - Rusdi, Dianna; Setyaningsih, Rini (Jurnal Administrasi Pendidikan dan Konseling Pendidikan, 2024)
This study aims to analyze the implementation, supervision, and challenges of boarding school management at Madrasah Aliyah Negeri (MAN) 4 Muara Fajar Rumbai. The study employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation. Informants consist of the head of the madrasah, vice principals of curriculum and facilities, boarding school supervisors, and student boarders. Data were analyzed through reduction, presentation, and conclusion drawing, while data validity was ensured using source and technique triangulation. The findings indicate that the boarding school management at MAN 4 Muara Fajar Rumbai has implemented several flagship programs, such as English and Arabic language proficiency, as well as tahsin and tahfidz programs. Character development is conducted 24 hours a day, both at school and in the dormitory. Supervision is carried out formally through weekly routines and evaluations, as well as informally through remote communication during holidays. Challenges include limited facilities, students’ reluctance to stay in dormitories, burnout due to full-day programs, and technical issues in the dormitory environment, such as cleanliness, bullying, and facility damage. This study concludes that although the implementation of boarding school management is relatively effective, improvements in facilities and enhanced coaching strategies are necessary to address the challenges and improve students’ comfort. The findings of this study are expected to serve as a reference for the development of boarding school-based education systems in other institutions.